Behavioral addictions in early-onset Parkinson disease are associated with DRD3 variants. (April 2018) - Castro-Martínez, Xochitl Helga; García-Ruiz, Pedro J.; Martínez-García, Carlos; Martínez-Castrillo, Juan Carlos; Vela, Lydia; Mata, Marina; Martínez-Torres, Irene; Feliz-Feliz, Cici; Palau, Francesc; Hoenicka, Janet
Abstract: Background: Impulse control disorders (ICDs) comprise abnormal behaviors frequently found in patients with Parkinson's disease (PD) receiving antiparkinsonian medication. ICDs in PD would develop when dopaminergic treatment overstimulates the dopamine receptor D3 (DR3). Here we studied whether DR3 gene ( DRD3 ) is associated to ICD in PD patients with early-onset (EOPD). Methods: We performed association analysis of the rs6280 DRD3 single nucleotide variation (SNV) (Ser9Gly) in a clinical sample of 126 non early-onset PD (NEOPD) and 73 EOPD (age at onset < 45). ICD was evaluated using the Questionnaire for Impulsive-Compulsive Disorders (QUIP) in PD. Results: In the total sample, we found that a younger onset of PD is linked to ICD traits with a potentially addictive reinforcement (ICDARs, behavioral addictions) ( p = .017) and a trend for total ICDs ( p = .078) while punding was not associated ( p = .75). EOPD sample showed an increase of DRD3 C+ genotype for ICD ( p = .022) and ICDARs ( p = .043) but not for punding ( p = .170). The post-hoc analyses including the time of evolution and Pramipexol or Ropinirole treatments, confirmed the independent effect of the DRD3 upon ICDs ( p = .028) and ICDARs ( p = .041) as well as the interaction between DRD3 and Pramipexol treatment upon ICDARs (OR = 4.60, 95% CI 1.20–17.632, p = .026). The NEOPD group showed no association between DRD3 and ICDs. Conclusions: We found that behavioral addictions in PD are associated with an early onset of the disease, the rs6280 DRD3 SNV and the type of dopamine agonist. Further investigation in independent samples is warranted. Highlights: DRD3 is associated with behavioral addictions in early-onset PD patients and not in non-early PD patients. The type of dopamine agonist may contribute to DRD3 association with behavioral addiction in patients with early-onset PD. DRD3 is not associated with punding in PD.